Analysis of factors determining invasion into attacking areas and the creation of goal-scoring opportunities in the Asian Cup football competition - Mahoney, L. E.; Wheeler, K. W.; Lyons, K. (Asian Journal of Exercise & Sports Science, 2012)
Performance analysis examined the determinants of invading the attacking zone and scoring goals in football. Performance analysis coded every attacking possession (N = 5531) during the 2011 Asian Cup. Variables assessed passing strategies, field position, and possession outcome. Chi-squared tests analysed associations between variables and standard residuals (SR) measured the strength of associations. A goal was more likely to occur when possession ended in the attacking zone (79% of goals, SR = 6.8). Binary logistic regression indicated start location, directness of play, final pass zone, and final pass channel as the primary determinants of possessions ending in the attacking zone. Possessions were likely to end in the attacking zone if they started in the attacking (N = 205, SR = 13.9) or pre-attacking (N = 566, SR = 7.7) zones. Direct passing was shown to increase the likelihood of a possession to end in the attacking zone if it started in the defensive zone (N = 73, SR = 3.1). The study concluded that possessions both start and end in the attacking zone for goal scoring success. Coaches should use fast counterattacks from the central channel and develop tactics to increase the probability of winning possession in the attacking zone.